Tokens or Stakeholders in Global Migration Governance? The Role of Affected Communities and Civil Society in the Global Compacts on Migration and Refugees - Stefan Rother; Elias Steinhilper (International Migration, 2019)
Focussing on the inclusion of those primarily affected as stakeholders (refugees and other migrants), this article addresses a key ambition of the compacts themselves. We employ an `inside-outside' perspective and firstly ask: which groups participated in the consultative processes, what agenda did they set `inside' the meetings, what alliances did they establish and how did they influence the outcomes? Secondly, we investigate what kind of advocacy took place `outside' of these formalized spaces and what impact it had? By this, we not only contribute to an evaluation of the processes themselves, but also advance current academic debates on strategies, spaces and political opportunity structures for civil society and particularly migrant involvement in global migration governance from below and the larger debate on democratizing global institutions.
Keywords: 300